The First Exhibition of Turkish Painting and Publications in the Kingdom of Yugoslavia in 1937 - Virijević, Vladan A. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
An exhibition of Turkish fine art and printed publications was held at the Prince Paul Museum in Belgrade from April 14 to 30, 1937. This event provided an opportunity for the Yugoslav cultural public to become acquainted for the first time with the artistic achievements of the artists of the Republic of Turkey during the first fifteen years of its existence. In addition to paintings, various exhibits representing the cultural heritage of the Ottoman Empire period were also displayed. According to art critics and the professional public, the artistic expression and themes of Turkish painters showed the influence of various European painting trends, resulting from their education in the leading art centres of Central and Western Europe. Mostly realistic depictions dominated, such as landscapes, still lifes, and portraits, with an emphasis on specific colours and motifs derived from the concept of Turkish nationalism—one of the pillars on which the Kemalism ideology rested. The exhibition was also a manifestation of the close bilateral relations between the Kingdom of Yugoslavia and the Republic of Turkey, so it can be said that it had specific political significance, contributing to the further strengthening and deepening of their relationship.
Keywords: exhibition; painting; publications; Kingdom of Yugoslavia; Republic of Turkey; Prince Paul Museum